Experimental research and analysis of modularity and robustness in target control efficiency of complex networks. (4th April 2022) - Shahsavari, Mona; Moeini, Ali; Shabankhah, Mahmood; Kamandi, Ali
Studies on overall target control of directed networks from the point of view of diversity have revealed that random target control of real-world networks is in general not efficient. Therefore, one needs to search for those features of the network which have a positive effect on the efficiency of random target control. In this paper, we investigate in particular the modularity of the Erdös-Rényi and Scale-Free directed networks. We observe that in these types of networks one could modify the efficiency of target control by increasing the network modularity while keeping the degree distribution fixed. We also notice that the impact of modularity on target control of such networks depends on many factors including number and size of communities of the network as well as network 'prior' target control efficiency. Moreover, we show that target control efficiency of the network grows when there is some link failure. It is a surprising fact that directed networks respond more robustly to target control than to full control. Numerical simulations support our claim for random target control of directed networks.